2015
DOI: 10.1016/j.chieco.2014.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Yuan and Roubles: Comparing wage determination in urban China and Russia at the beginning of the new millennium

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
2
4
0
1
Order By: Relevance
“…In contrast, seniority played a larger role for wage levels in urban China than in Russia. Gustafsson et al (2015) made a similar comparison using Chinese data for 2002 and Russian data for 2003, and were thus able to look at changes since the end of the 1980s. The results showed that wage inequality had risen equally rapidly in the urban regions of both countries, and the association between years of schooling and earnings had strengthened.…”
Section: The Literaturementioning
confidence: 99%
“…In contrast, seniority played a larger role for wage levels in urban China than in Russia. Gustafsson et al (2015) made a similar comparison using Chinese data for 2002 and Russian data for 2003, and were thus able to look at changes since the end of the 1980s. The results showed that wage inequality had risen equally rapidly in the urban regions of both countries, and the association between years of schooling and earnings had strengthened.…”
Section: The Literaturementioning
confidence: 99%
“…By the late 1990s and early 2000s, Hansberry () indicates that the gap was the lowest at the top; yet the evidence in Atencio and Posadas () and Gustafsson et al . () indicates the opposite. For the most recent period, the evidence is also indicative of the widest gap in the middle (Atencio and Posadas, ) or at the top of the pay distribution (ILO, ), in line with the presence of the glass‐ceiling effect.…”
Section: Gender Pay Gaps At the Mean And Across The Pay Distributionmentioning
confidence: 99%
“…Мотивы продолжения трудовой деятельности после выхода на пенсию достаточно подробно освещены как в отечественных [8], так и зарубежных источниках [14,15,17,19]. Основными среди них являются:…”
Section: основная частьunclassified